217k views
1 vote
Operations with rational expressions

Operations with rational expressions-example-1
User Iboboboru
by
5.6k points

1 Answer

2 votes


$(50-2 w^(2))/(3 w^(2)+9 w-30) \cdot (w^(2)+5 w-14)/(6 w-30)=-(w+7)/(9)

Solution:

Given expression:


$(50-2 w^(2))/(3 w^(2)+9 w-30) \cdot (w^(2)+5 w-14)/(6 w-30)

To solve the given expression:

First simplify:
(50-2 w^(2))/(3 w^(2)+9 w-30)


$(50-2 w^(2))/(3 w^(2)+9 w-30)=-(2(w+5)(w-5))/(3(w-2)(w+5))

Cancel the common factor (w + 5).


$=-(2(w-5))/(3(w-2))

Now substitute this in the given expression.


$(50-2 w^(2))/(3 w^(2)+9 w-30) \cdot (w^(2)+5 w-14)/(6 w-30)=-(2(w-5))/(3(w-2)) \cdot (w^(2)+5 w-14)/(6 w-30)

Multiply the fractions
(a)/(b) \cdot (c)/(d)=(a \cdot c)/(b \cdot d)


$=-(2(w-5)\left(w^(2)+5 w-14\right))/(3(w-2)(6 w-30))

Factor the denominator
3(w-2)(6 w-30) =18(w-2)(w-5)


$=-(2(w-5)\left(w^(2)+5 w-14\right))/(18(w-2)(w-5))

Cancel the common factor 2(w – 5).


$=-(w^(2)+5 w-14)/(9(w-2))

Factor the numerator
w^(2)+5 w-14=(w-2)(w+7)


$=-((w-2)(w+7))/(9(w-2))

Cancel the common factor (w – 2).


$=-(w+7)/(9)


$(50-2 w^(2))/(3 w^(2)+9 w-30) \cdot (w^(2)+5 w-14)/(6 w-30)=-(w+7)/(9)

User Anna Poorani
by
5.0k points